Water absorption analysis on impregnated kenaf with nanosilica for epoxy/kenaf composite - Bajuri, Farid; Mazlan, Norkhairunnisa; Ishak, Mohamad Ridzwan (IOP Publishing, 2018)
Due to the existence of hydroxyl group from cellulose and hemicellulose in natural fibre, it has a high tendency to absorb significant amount of water. Nanosilica has high surface area due to its nanosize, which is capable to seal the fibre's pores. In this work, impregnation technique was used to fill the pores of kenaf fibre with nanosilica in order to reduce the water uptake of the resulting composite. To impregnate the randomly orientated kenaf fibres with nanosilica, the fibres were initially degassed in a plastic container to enable the inclusion of nanosilica to fill the fibre pores. Then nanosilica/epoxy mixture was infused into the container and left under vacuum condition for 24 hours. The hardener was then applied onto the fibres before being hot pressed to aid the curing process. For the water absorption test, the specimens were dried before being placed in a glass container filled distilled water and regularly weighed until approximately 80 days. Like any other kenaf reinforced epoxy, the specimens absorbed water at a rapid rate in the beginning before slowing down and approaching equilibrium. The maximum water absorption rates were 14.4% and 12.9% for specimens with composition of 50 vol% kenaf, 5 vol% nanosilica and 60 vol% kenaf, 5 vol% nanosilica, respectively. Specimens with nanosilica infused but not impregnated had shown a significantly higher water absorption rates at 24.5% and 29.6% respectively. These results show that nanosilica can help reduce the water absorption rate of the natural fibres by blocking the pores of the fibres rendering them unable to absorb water.